‘Whoever Gives Me Thorns and Thistles’: Rhetorical Ambiguity and the Use of ‭ןתי‬ ‭ימ‬ in Isaiah 27.2-6 - Johnson, Benjamin J. M. (Journal for the study of the Old Testament, 2011)
Isaiah 27.2-6, sometimes known as the ‘new song of the vineyard’, is a very difficult text. It has many textual oddities and it can be variously interpreted as a promise of salvation or a warning of judgment. This study proposes to alleviate some of the difficulties of Isa. 27.2-6 by reading them as an intentional device of rhetorical ambiguity which causes readers to reassess as they read. Specifically, it is suggested that the phrase ‭יננתי־ימ‬, most frequently understood as an optative idiom, ‘O that I had’, should rather be understood in this context as a simple indefinite and translated: ‘whoever gives me’. It is argued that this interpretation of the phrase ‭ןתי‬ ‭ימ‬ is both grammatically plausible and makes the most sense of this new song of the vineyard.